2013
DOI: 10.2965/jwet.2013.21
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chelating Agents on Fenton-Type Reaction Using Ferrous Ion and Hypochlorous Acid

Abstract: Iron-based advanced oxidation technologies, such as the Fenton process, are widely used for industrial wastewater treatment. However, wastewater sometimes contains chelating agents such as detergents, stabilizers, and masking agents for metallic ions, which have a potential to inhibit the iron-based advanced oxidation process through the masking of iron. In this research, we investigated the influence of chelating agents on Fenton-type reaction using ferrous ion (Fe 2+ ) and hypochlorous acid (HOCl). Chel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Li et al (2007) investigated the effect of EDTA on • OH production during Fenton reaction, and the result showed that EDTA did not affect • OH generation monitored by HPLC assay, but from the electron spin resonance (ESR) spin-trapping measurement, it was showed that EDTA suppresses hydroxyl radical formation. Kishimoto et al reported that iron-chelating agents, such as EDTA, strongly inhibited (70%) the Fenton reaction at pH 2.5 or higher by complex formation with Fe(II) ion and masking of iron (Kishimoto et al 2013). Similar inconsistent results were observed by Wang et al (2011), who observed correlated well with the accelerated • OH formation from the H 2 O 2 decomposition at the BiFeO3 surface.…”
Section: Effect Of Scavengersmentioning
confidence: 99%
“…Li et al (2007) investigated the effect of EDTA on • OH production during Fenton reaction, and the result showed that EDTA did not affect • OH generation monitored by HPLC assay, but from the electron spin resonance (ESR) spin-trapping measurement, it was showed that EDTA suppresses hydroxyl radical formation. Kishimoto et al reported that iron-chelating agents, such as EDTA, strongly inhibited (70%) the Fenton reaction at pH 2.5 or higher by complex formation with Fe(II) ion and masking of iron (Kishimoto et al 2013). Similar inconsistent results were observed by Wang et al (2011), who observed correlated well with the accelerated • OH formation from the H 2 O 2 decomposition at the BiFeO3 surface.…”
Section: Effect Of Scavengersmentioning
confidence: 99%
“…demonstrated that “the 1:1 iron complexes of EDTA, DTPA, and citrate clearly induce the reduction of H 2 O 2 .” However, Kishimoto et al . discovered that the extent to which Fenton systems were inhibited to degrade 1,4‐dioxane in the presence of oxalate and EDTA decreased as solution pH fell below 6, that is, as the degree of complexation also deceased at lower, acidic pH values, implying that only unchelated Fe(II) ions can be oxidized further.…”
Section: Description Of Treatment Technologiesmentioning
confidence: 99%
“…The solution in the reactor was mixed with a magnetic stirrer during the run, and each run continued for 30-45 minutes. The concentration of 1,4-dioxane was determined by high-performance chromatography with a refractive index detector [21]. Since the total volume of diluted sulphuric acid and sodium hydroxide solution added to the reactor for pH control was less than 10 mL, the hypochlorite and 1,4-dioxane concentrations obtained by the chemical analysis were not corrected for discussion.…”
Section: Absorbance Spectrum Of the Hypochlorite Solutionmentioning
confidence: 99%